Synthesis of rare-earth metal and rare-earth metal-fluoride nanoparticles in ionic liquids and propylene carbonate - Siebels, Marvin; Mai, Lukas; Schmolke, Laura; Schütte, Kai; Barthel, Juri; Yue, Junpei; Thomas, Jörg; Smarsly, Bernd M.; Devi, Anjana; Fischer, Roland A.; Janiak, Christoph (Beilstein Journal of Nanotechnology, 2018)
Decomposition of rare-earth tris(N,N′-diisopropyl-2-methylamidinato)metal(III) complexes [RE{MeC(N(iPr)2)}3] (RE(amd)3; RE = Pr(III), Gd(III), Er(III)) and tris(2,2,6,6-tetramethyl-3,5-heptanedionato)europium(III) (Eu(dpm)3) induced by microwave heating in the ionic liquids (ILs) 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIm][BF4]), 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([BMIm][NTf2]) and in propylene carbonate (PC) yield oxide-free rare-earth metal nanoparticles (RE-NPs) in [BMIm][NTf2] and PC for RE = Pr, Gd and Er or rare-earth metal-fluoride nanoparticles (REF3-NPs) in the fluoride-donating IL [BMIm][BF4] for RE = Pr, Eu, Gd and Er. The crystalline phases and the absence of significant oxide impurities in RE-NPs and REF3-NPs were verified by powder X-ray diffraction (PXRD), selected area electron diffraction (SAED) and high-resolution X-ray photoelectron spectroscopy (XPS). The size distributions of the nanoparticles were determined by transmission electron microscopy (TEM) and high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) to an average diameter of (11 ± 6) to (38 ± 17) nm for the REF3-NPs from [BMIm][BF4]. The RE-NPs from [BMIm][NTf2] or PC showed diameters of (1.5 ± 0.5) to (5 ± 1) nm. The characterization was completed by energy-dispersive X-ray spectroscopy (EDX).
Keywords: ionic liquids; metal amidinates; rare-earth metal-fluoride nanoparticles; rare-earth metal nanoparticles; soft wet-chemical synthesis

(untitled) - Ghobadi, M.; Gharabaghi, M.; Abdollahi, H.; Kisomi, A. S. (New J. Chem., 2017)

(untitled) - Das, N.; Das, D. (J. Rare Earths, 2013)

(untitled) - Eliseeva, S. V.; Bünzli, J.-C. G. (New J. Chem., 2011)

(untitled) - Escudero, A.; Carrillo-Carrion, C.; Zyuzin, M. V.; Parak, W. J. (Top. Curr. Chem., 2016)

(untitled) - Bouzigues, C.; Gacoin, T.; Alexandrou, A. (ACS Nano, 2011)

(untitled) - Nelson, J. A.; Bennett, L. H.; Wagner, M. J. (J. Am. Chem. Soc., 2002)

(untitled) - Hansen, P.; Clausen, C.; Much, G.; Rosenkranz, M.; Witter, K. (J. Appl. Phys., 1989)

(untitled) - Mai, H.-X.; Zhang, Y.-W.; Si, R.; Yan, Z.-G.; Sun, L.-d.; You, L.-P.; Yan, C.-H. (J. Am. Chem. Soc., 2006)

(untitled) - Schütte, K.; Meyer, H.; Gemel, C.; Barthel, J.; Fischer, R. A.; Janiak, C. (Nanoscale, 2014)

(untitled) - Bahlawane, N.; Kohse-Höinghaus, K.; Premkumar, P. A.; Lenoble, D. (Chem. Sci., 2012)

(untitled) - Kim, M. R.; Xu, Z.; Chen, G.; Ma, D. (Chem. – Eur. J., 2014)

(untitled) - Schmitz, A.; Schütte, K.; Ilievski, V.; Barthel, J.; Burk, L.; Mülhaupt, R.; Yue, J.; Smarsly, B.; Janiak, C. (Beilstein J. Nanotechnol., 2017)

(untitled) - Barker, J.; Kilner, M. (Coord. Chem. Rev., 1994)

(untitled) - Schuchmann, D.; Westphal, U.; Schulz, S.; Flörke, U.; Bläser, D.; Boese, R. (Angew. Chem., 2009)

(untitled) - Dagorne, S.; Guzei, I. A.; Coles, M. P.; Jordan, R. F. (J. Am. Chem. Soc., 2000)

(untitled) - Sita, L. R.; Babcock, J. R. (Organometallics, 1998)

(untitled) - Krisyuk, V.; Aloui, L.; Prud’homme, N.; Sysoev, S.; Senocq, F.; Samélor, D.; Vahlas, C. (Electrochem. Solid-State Lett., 2011)

(untitled) - Moni, P.; Al-Obeidi, A.; Gleason, K. K. (Beilstein J. Nanotechnol., 2017)

(untitled) - Komissarov, I. V.; Kovalchuk, N. G.; Labunov, V. A.; Girel, K. V.; Korolik, O. V.; Tivanov, M. S.; Lazauskas, A.; Andrulevicius, M.; Tamulevicius, T.; Grigaliunas, V.; Meskinis, S.; Tamulevicius, S.; et al. (Beilstein J. Nanotechnol., 2017)

(untitled) - Coyle, J. P.; Monillas, W. H.; Yap, G. P. A.; Barry, S. T. (Inorg. Chem., 2008)

(untitled) - Taubert, A. (Acta Chim. Slov., 2005)

(untitled) - Waltz, F.; Swider, A. M.; Hoyer, P.; Hassel, T.; Erne, M.; Möhwald, K.; Adlung, M.; Feldhoff, A.; Wickleder, C.; Bach, F.-W.; Behrens, P. (J. Mater. Sci., 2012)

(untitled) - Yan, C.; Wagner, M. J. (Nano Lett., 2013)

(untitled) - Furukawa, S.; Komatsu, T. (ACS Catal., 2017)

(untitled) - Greeley, J.; Stephens, I. E. L.; Bondarenko, A. S.; Johansson, T. P.; Hansen, H. A.; Jaramillo, T. F.; Rossmeisl, J.; Chorkendorff, I.; Nørskov, J. K. (Nat. Chem., 2009)

(untitled) - Kanady, J. S.; Leidinger, P.; Haas, A.; Titlbach, S.; Schunk, S.; Schierle-Arndt, K.; Crumlin, E. J.; Wu, C. H.; Alivisatos, A. P. (J. Am. Chem. Soc., 2017)

(untitled) - Campbell, P. S.; Prechtl, M. H. G.; Santini, C. C.; Haumesser, P.-H. (Curr. Org. Chem., 2013)

(untitled) - Freudenmann, D.; Wolf, S.; Wolff, M.; Feldmann, C. (Angew. Chem., Int. Ed., 2011)

(untitled) - Ahmed, E.; Breternitz, J.; Groh, M. F.; Ruck, M. (CrystEngComm, 2012)

(untitled) - Ahmed, E.; Ruck, M. (Dalton Trans., 2011)

(untitled) - Groh, M. F.; Müller, U.; Ahmed, E.; Rothenberger, A.; Ruck, M. (Z. Naturforsch., B, 2013)

(untitled) - Janiak, C. (Z. Naturforsch., B, 2013)

(untitled) - Marquardt, D.; Janiak, C. (Nachr. Chem., 2013)

Nanoparticles - Schmid, G. (Wiley-VCH, 2004)

(untitled) - Antonietti, M.; Kuang, D.; Smarsly, B.; Zhou, Y. (Angew. Chem., Int. Ed., 2004)

(untitled) - Astruc, D.; Lu, F.; Aranzaes, J. R. (Angew. Chem., Int. Ed., 2005)

(untitled) - Kaper, H.; Endres, F.; Djerdj, I.; Antonietti, M.; Smarsly, B. M.; Maier, J.; Hu, Y.-S. (Small, 2007)

(untitled) - Wasserscheid, P.; Keim, W. (Angew. Chem., Int. Ed., 2000)

(untitled) - Bayardon, J.; Holz, J.; Schäffner, B.; Andrushko, V.; Verevkin, S.; Preetz, A.; Börner, A. (Angew. Chem., 2007)

(untitled) - Verevkin, S. P.; Emel’yanenko, V. N.; Toktonov, A. V.; Chernyak, Y.; Schäffner, B.; Börner, A. (J. Chem. Thermodyn., 2008)

(untitled) - Schäffner, B.; Verevkin, S. P.; Börner, A. (Chem. Unserer Zeit, 2009)

(untitled) - Schütte, K.; Barthel, J.; Endres, M.; Siebels, M.; Smarsly, B. M.; Yue, J.; Janiak, C. (ChemistryOpen, 2017)

(untitled) - Archer, D. G.; Widegren, J. A.; Kirklin, D. R.; Magee, J. W. (J. Chem. Eng. Data, 2005)

(untitled) - Freire, M. G.; Neves, C. M. S. S.; Marrucho, I. M.; Coutinho, J. A. P.; Fernandes, A. M. (J. Phys. Chem. A, 2010)

(untitled) - Rutz, C.; Schmolke, L.; Gvilava, V.; Janiak, C. (Z. Anorg. Allg. Chem., 2017)

(untitled) - Olchowka, J.; Suta, M.; Wickleder, C. (Chem. – Eur. J., 2017)

(untitled) - Lorbeer, C.; Behrends, F.; Cybinska, J.; Eckert, H.; Mudring, A.-V. (J. Mater. Chem. C, 2014)

Thermo Scientific XPS: Knowledge Base

Handbook of X–ray Photoelectron Spectroscopy - Moulder, J. F.; Stickle, W. F.; Sobol, P. E.; Bomben, K. D. (Perkin–Elmer Corporation, 1992)

(untitled) - Raiser, D.; Deville, J. P. (J. Electron Spectrosc. Relat. Phenom., 1991)

(untitled) - Antipov, E. V.; Khasanova, N. R.; Fedotov, S. S. (IUCrJ, 2015)

(untitled) - Poizot, P.; Laruelle, S.; Grugeon, S.; Dupont, L.; Tarascon, J.-M. (Nature, 2000)

(untitled) - Tarascon, J.-M.; Armand, M. (Nature, 2001)

(untitled) - Breitung, B.; Reddy, M. A.; Chakravadhanula, V. S. K.; Engel, M.; Kübel, C.; Powell, A. K.; Hahn, H.; Fichtner, M. (Beilstein J. Nanotechnol., 2013)

(untitled) - Yamakawa, N.; Jiang, M.; Key, B.; Grey, C. P. (J. Am. Chem. Soc., 2009)

(untitled) - Bilecka, I.; Niederberger, M. (Nanoscale, 2010)

(untitled) - Chen, W.; Gutmann, B.; Kappe, C. O. (ChemistryOpen, 2012)

(untitled) - Rodríguez, A. M.; Prieto, P.; de la Hoz, A.; Díaz-Ortíz, A.; Martín, R.; García, J. I. (ChemistryOpen, 2015)

(untitled) - Schütte, K.; Doddi, A.; Kroll, C.; Meyer, H.; Wiktor, C.; Gemel, C.; van Tendeloo, G.; Fischer, R. A.; Janiak, C. (Nanoscale, 2014)

(untitled) - Krasnopolski, M.; Hrib, C. G.; Seidel, R. W.; Winter, M.; Becker, H.-W.; Rogalla, D.; Fischer, R. A.; Edelmann, F. T.; Devi, A. (Inorg. Chem., 2013)

Metalorganic chemical vapor deposition (MOCVD) routes for fabrication of rare earth nitride thin films : precursor evaluation, thin film deposition and characterization - Krasnopolski, M. (Ruhr-Universität Bochum, 2014)

(untitled) - Lim, B. S.; Rahtu, A.; Park, J.-S.; Gordon, R. G. (Inorg. Chem., 2003)

(untitled) - Schmidt, S.; Schulz, S.; Bläser, D.; Boese, R.; Bolte, M. (Organometallics, 2010)

(untitled) - Zhou, J.; Zhang, D.; Zhang, X.; Song, H.; Chen, X. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Makinson, J. D.; Lee, J. S.; Magner, S. H.; De Angelis, R. J.; Weins, W. N.; Hieronymus, A. S. (Adv. X-Ray Anal., 2000)

(untitled) - Kurian, M.; Kunjachan, C. (Nano-Struct. Nano-Objects, 2015)

(untitled) - Zhang, F.; Chan, S.-W.; Spanier, J. E.; Apak, E.; Jin, Q.; Robinson, R. D.; Herman, I. P. (Appl. Phys. Lett., 2002)

(untitled) - Reddy, K. M.; Manorama, S. V.; Reddy, A. R. (Mater. Chem. Phys., 2003)

(untitled) - Manhas, M.; Kumar, V.; Sharma, V.; Ntwaeaborwa, O. M.; Swart, H. C. (Nano-Struct. Nano-Objects, 2015)

(untitled) - Ernst Ruska-Centre for Microscopy and Spectroscopy with Electrons (ER-C) (J. Large-Scale Res. Facil., 2016)

(untitled) - Ernst Ruska-Centre for Microscopy and Spectroscopy with Electrons (ER-C) (J. Large-Scale Res. Facil., 2016)